A land use model of the effects of eco-labeling in coffee markets - Heidkamp, Patrick; Hanink, Dean M.; Cromley, Robert G. (Annals of Regional Science, 2008)
International non-profit organizations have started to implement eco-labeling for credence attributes programs aimed to inform consumers about environmentally sound or “sustainable” production standards for various products. Using coffee labeled as “shade grown” or “bird friendly” as an example, this paper describes the impact such labeling programs may have on local land use patterns in coffee producing regions. Shade grown coffee farms should provide a variety of external benefits, including the preservation of biodiversity, carbon sequestration, the prevention of soil erosion and aquifer recharge. Those externalities, however, are not expected to have observable land use impacts unless they are capitalized in the coffee market. The prospect of market capitalization of externalities suggests the extension of the conventional von Thunen model to the calculation of social location rent. Using the maximization of social location rent as a criterion allows the externality effect to play a direct role in market-based land use allocation of land between eco-labeled shade grown coffee production and other activities.
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-655-160-683-062 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Aves; agricultural market; coffee; crop production; dept.egm; ecolabeling; land use; modeling

Offshore threats: Liquefied natural gas, terrorism, and environmental debate in Connecticut - Harrison, Blake (Annals of The Association of American Geographers, 2008)
Broadwater Energy is one of a number of recent proposals to construct a liquefied natural gas facility along the East Coast of the United States. The proposal calls for the construction of an import and regasification terminal in Long Island Sound, roughly halfway between the states of New York and Connecticut. First made public in 2004 by its sponsors, TransCanada and Shell, the Broadwater proposal has inspired opposition from a range of interest groups. An examination of the Broadwater debate with a focus on arguments made by Connecticut residents in the months leading up to the release in late 2006 of the proposal's Draft Environmental Impact Statement reveals explicit and implicit points of overlap between concerns about the facility's environmental impacts and concerns about its status as a potential terrorist target. Discussions about terrorism deployed in the Broadwater debate have initiated and informed a politics of scale through which themes common to environmental debates have been transformed. This transformation, in turn, highlights the discursive and material influence of terrorism in contemporary U.S. society. Concerns about terrorist attacks have been deployed by activists to enhance the strength of an otherwise environmental debate and, in the process, those concerns have developed the potential to shape land use policy in Long Island Sound. Key Words: environmentalism, liquefied natural gas, Long Island Sound, scale, terrorism.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/056-913-849-043-885 tex.unique-id: [object Object]
Keywords: Connecticut; Environmentalism; Liquefied natural gas; Long Island Sound; North America; Scale; Terrorism; United States; container terminal; dept.egm; environmental impact; environmental policy; environmentalism; land use planning; liquefied natural gas; offshore engineering; terrorism

Indian geography: voice of concern - Martin, Geoffrey J. (The Professional Geographer, 2008)
Keywords: dept.egm; ⛔ No DOI found

Transfer of saracha weberbaueri dammer subspecies pallascana bitter, also known as saracha pallascana (bitter) macbride, to jaltomata pallascana (bitter) mione (solanaceae) - Mione, Thomas; Gonzalez, Segundo Leiva; Yacher, Leon (Arnaldoa, 2008)
Citation Key Alias: lens.org/153-726-006-094-847 tex.type: [object Object]
Keywords: dept.egm; ⛔ No DOI found

World's rarest bird? The long-whikered owlet of peru - Smith, Dwight G; Yacher, Leon (Arnaldoa, 2008)
Citation Key Alias: lens.org/059-423-042-312-359 tex.type: [object Object]
Keywords: dept.egm; ⛔ No DOI found